Penerapan Marketing Mix sebagai Strategi Pemasaran Jasa Pendidikan di MAN 1 Yogyakarta - Labaso, Syahrial (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2018)
Abstract This study examines the strategies implemented for education marketing services in Islamic education institutions. This research is motivated by the efforts to develop the quality of Islamic education institutions, so that they could compete with other organizations. Education marketing services are intended to create a conducive and stable marketing condition, so as to have a positive impact on the parties involved in the marketing process (both the school as the producer and the community as consumers). Based on the results of the study, which was conducted at the Madrasah Aliyah Negeri (MAN) 1 Yogyakarta, it was found that Islamic education institutions also implement various strategies in marketing their educational services. The marketing strategy in MAN 1 Yogyakarta is carried out through the application of marketing mix theory (products, prices, places, promotions, human resources, physical evidence, and processes) by utilizing its superior competences as an Islamic educational institution that tends to have moderate ideology, so it can target Muslim communities both from traditional and modern backgrounds as the marketing segment of their educational services. Keywords: Marketing Mix, Marketing Strategy, Education Services